Proyecto fotográfico, “Ecos del Pasado”, una transmediación del juego a la realidad icónica - Carpio Ferrando, Jeancarlo Sebastian (2021)
The project began in 2014 as a campaign for the Dungeons & Dragons (D&D) roleplaying game. The heroes that were created to be part of this campaign of the wellknown role-playing game, which lasted 3 years and inspired a session that seeks to portray them as we imagine them in their reality, adopting poses, forms and attitudes or showing their mastery of what we know as magic. That is to say, the construction of characters, from art to acting, took more than 3 years of preparation, since it is based on designs taken from different historical, artistic and video game sources that inspired both the history of the world (original world created specially to play this campaign) and its inhabitants, including our characters. The project has 4 characters, treated with digital photomontage effects to give them realism, seeking to transfer the personality, concepts, tones and atmospheres of the spaces and characters of a D&D game campaign to the photographic environment, building new images based on the technical and communicative qualities of this medium, production and art direction, character direction and the intervention of cosplay as an activity or fashion close and accepted by the target audience of video games, anime, film and role-playing games. This project will be disseminated through digital platforms such as Instagram and Behance.